Editorial - de Bot, Kees; Bátyi, Szilvia (Studies in Second Language Learning and Teaching, 2017)
Teachers have known for a long time that language learners differ and that a one-size-fits-all does not exist. Still in the days of structuralism, language and its users were seen as being a “thing” to be learned and taught, and since the goal of the learning was the same for all learners—proficiency in the language—the road to that goal should be uniform as well. Language was seen as a set of structures that had to be mastered, and this led to the audio-lingual method in which learners had to drill patterns and make no mistakes, since mistakes could be engrained as good as correct patterns. It was argued that the audiolingual method allowed for individual variation, since learners could choose their own goals and repeat parts of the curriculum on their own.